Coherent optical communication systems in digital signal processing - Nordin, Khairussakinah; Hashim, Nik Mohd Zarifie; Idris, Suhana; Darsono, Abd Majid; Salleh, Azahari; Mohamad, Najmiah Radiah (IJSRET, 2014)
For the future of optical communication systems, Digital signal processing (DSP) is an enabling technology. This system is the most promising widely viewed in the next generation for long-haul transport systems. In past, the digital carrier phase estimation demonstration in coherent receivers has stimulated an extensive attention in coherent optical communications again. In this paper, the emergence of DSP tutorial will discussed before surveying in the algorithms required in digital coherent transceivers for optical communication systems.